AGE AS AN IMPORTANT FACTOR AFFECTING THE PROCESS OF SECOND LANGUAGE ACQUISITION : A LITERATURE REVIEW - Aria Septi Anggaira (HOLISTICS, 2015)
Second language (L2) learners are different. They learn with different speed and different results. There are many explanations for that issue. The general factors that influence second language learning are: age, aptitude and intelligence, cognitive style, attitudes, motivation and personality. The aim of this article is to present age as one of the internal factor and its contribution to success or failure in language learning.